Prophetic Sira and the Construction of Indonesian Islam - Karim, Muhammad Abdul (IJISH (International Journal of Islamic Studies and Humanities), 2021)
Indonesian Islam has gone through a long journey in its history since the first advent up to the present day. In this course, one should note that the process of Islamization was formed under a set of historical and cultural complexity. Among those, the role of Islamic preaching is the most important. Under this canopy, the process of transmission and transformation took the first place as the main force. As the Qur’an and Sunna are the major sources for all Muslims around the world. Both had also become the main streams in Islamicization. Seerat-e-nabi, beside the Qur’an, in this case has a place of honor. It became one of the major sources of all Islamic heritages in Indonesia. The prophet Muhammad PBUH (peace be upon him) was immersed within the Indonesian Islamic traditions in various fields and spheres. It is fair to say that the story of the islamicization of the Indonesian archipelago and the face of Indonesian Islam today is culturally formed by the determination of seerat-e-nabi, besides the Qur’anic scripture. In the other words, the birth and the face of Islam really depend on how its adherents interpret and take a cultural reception on the seerat-e-nabi. This paper tries to capture the prophetic heritage in Indonesian Islam in twofold analysis; transmission and transformation. The former tries to explore how the heritage of seerat-e-nabi flowed into the scene of Indonesian moslem life through various modes of transmission up to the present day. The latter aims at how the seerat-e-nabi became the force and inspiration for the various receptions of institutional matters.